Scents and Scent Ability: Can Snakes Identify Heterospecifics and Conspecifics Using Airborne Semiochemicals? - Rulon W. Clark; Harshita Vallabhaneni; Hana M. Koyama; Elisa J. Paider; Donald M. Walker; Jason W. Dallas (Journal of Chemical Ecology, 2026)

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Ranavirus infection does not reduce heat tolerance in a larval amphibian - Jason W. Dallas; Robin W. Warne (Journal of Thermal Biology, 2023)

Ecology of the synanthropic mediterranean house gecko (Hemidactylus turcicus) at their northern invasion front - Jason W. Dallas; Allison Harris; Jacob Reinbolt; Robin W. Warne (Urban Ecosystems, 2022)

Microbial anhydrobiosis - Jason Bosch; Gilda Varliero; John E. Hallsworth; Tiffany D. Dallas; David Hopkins; Beat Frey; Weidong Kong; Pedro Lebre; Thulani P. Makhalanyane; Don A. Cowan (Environmental Microbiology, 2021)
Summary The loss of cellular water (desiccation) and the resulting low cytosolic water activity are major stress factors for life. Numerous prokaryotic and eukaryotic taxa have evolved molecular and physiological adaptions to periods of low water availability or water‐limited environments that occur across the terrestrial Earth. The changes within cells during the processes of desiccation and rehydration, from the activation (and inactivation) of biosynthetic pathways to the accumulation of compatible solutes, have been studied in considerable detail. However, relatively little is known on the metabolic status of organisms in the desiccated state; that is, in the sometimes extended periods between the drying and rewetting phases. During these periods, which can extend beyond decades and which we term ‘anhydrobiosis’, organismal survival could be dependent on a continued supply of energy to maintain the basal metabolic processes necessary for critical functions such as macromolecular repair. Here, we review the state of knowledge relating to the function of microorganisms during the anhydrobiotic state, highlighting substantial gaps in our understanding of qualitative and quantitative aspects of molecular and biochemical processes in desiccated cells.

Taxonomy, not locality, influences the cloacal microbiota of two nearctic colubrids: a preliminary analysis - Jason W. Dallas; Walter E. Meshaka; Lydia Zeglin; Robin W. Warne (Molecular Biology Reports, 2021)

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

Heme oxygenase-1 regulates cell proliferation via carbon monoxide-mediated inhibition of T-type Ca2+ channels - Hayley Duckles; Hannah E. Boycott; Moza M. Al-Owais; Jacobo Elies; Emily Johnson; Mark L. Dallas; Karen E. Porter; Francesca Giuntini; John P. Boyle; Jason L. Scragg; Chris Peers (Pflügers Archiv - European Journal of Physiology, 2015)

Self-injurious behaviours are associated with alterations in the somatosensory system in children with autism spectrum disorder - Emma G. Duerden; Dallas Card; S. Wendy Roberts; Kathleen M. Mak-Fan; M. Mallar Chakravarty; Jason P. Lerch; Margot J. Taylor (Brain Structure and Function, 2014)